Chemical Vapor Deposition - Recent Advances and Applications in Optical, Solar Cells and Solid State Devices 2016
DOI: 10.5772/63012
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Rich Oxide Obtained by Low-Pressure Chemical Vapor Deposition to Develop Silicon Light Sources

Abstract: Off stoichiometric silicon oxide, also known as silicon-rich oxide (SRO), is a lightemitting material that is compatible with silicon technology; therefore, it is a good candidate to be used as a light source in all-silicon optoelectronic circuits. The SRO obtained by low-pressure chemical vapor deposition (LPCVD) has shown the best luminescent properties compared to other techniques. In spite of LPCVD being a simple technique, it is not a simple task to obtain SRO with exact silicon excess in a reliable and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…As mentioned, it is generally accepted that the PL in SRO is caused by the combination of defect-related radiative centers, and quantum confinement phenomena. 6,8,9 In accordance to this, the experimental results were fitted to the sum of two Gaussian components. It was observed that the spectra is indeed composed by the contribution of two bands, hereafter referred to as PL 1 and PL 2 .…”
Section: B Photo Luminescence Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, it is generally accepted that the PL in SRO is caused by the combination of defect-related radiative centers, and quantum confinement phenomena. 6,8,9 In accordance to this, the experimental results were fitted to the sum of two Gaussian components. It was observed that the spectra is indeed composed by the contribution of two bands, hereafter referred to as PL 1 and PL 2 .…”
Section: B Photo Luminescence Spectramentioning
confidence: 99%
“…One of the most useful features of the SRO is the possibility of tuning the characteristics of its emission spectrum, which can comprehend nearly all the visible range, and is susceptible of modification trough the use of different fabrication techniques and conditions. 6,7 Whereas it has been reached a consensus in that the luminescence in these materials is caused by a combination of defect-related emission and quantum confinement phenomena, 6,8,9 it still exists a lack of a precise knowledge regarding how each contributes to the overall spectrum, and how this is related to the atomic characteristics of the material. Furthermore, the parameters used to define its characteristics are not common for all fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nano-structured Si-based materials has been demonstrated to be a viable alternative for producing fully monolithic electrophotonic systems obtained solely by complementary metal oxide semiconductor (CMOS) techniques [1,2,3]. In particular, light emitters using SixNy-SiOx nano-bilayers are promising for several applications, due to the combination of a wide visible spectrum and well-controlled photoluminescence (PL) provided by silicon-rich oxide (SRO) [2], and the possibility of improving efficiency [1], carrier injection due to lower energy barriers [4], and quantum yields [5] provided by silicon nitride and oxynitrides for electroluminescence (EL). On the other hand, planar waveguides (WG) transmitting injected or optically stimulated visible light have shown to be very promising for application in the field of integrated optical sensors and biosensors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a LPCVD reactor allows operating more varieties of precursors and reduces the incorporation of impurities in the as-deposited films [ 28 ]. The only differences are related to the process reactor that must withstand a high-pressure gradient and the insertion of a vacuum system at the exhaust point of the reactor [ 37 ].…”
Section: Chemical Vapor Synthesis Of Sic Films: From Cvd To Aldmentioning
confidence: 99%